2012
DOI: 10.4103/1947-2714.93889
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Patterns, and Factors Predicting Mortality of Abdominal Injuries in Trauma Patients

Abstract: Background:Abdominal trauma is a major public health problem for all nations and all socioeconomic strata.Aim:This study was designed to determine the incidence and patterns of abdominal injuries in trauma patients.Materials and Methods:We classified and identified the incidence and subtype of abdominal injuries and associated trauma, and identified variables related to morbidity and mortality.Results:Abdominal trauma was present in 248 of 300 cases; 172 patients with blunt abdominal trauma and 76 with penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 9 publications
7
40
2
1
Order By: Relevance
“…Similar findings were also reported by earlier studies [5,9]. The most common mechanism of injury in this study was blunt trauma (95%), this finding puts our study as the largest series with 1,036 TAI cases which exceeds the earlier published report on blunt TAI in the literature [9-11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were also reported by earlier studies [5,9]. The most common mechanism of injury in this study was blunt trauma (95%), this finding puts our study as the largest series with 1,036 TAI cases which exceeds the earlier published report on blunt TAI in the literature [9-11].…”
Section: Discussionsupporting
confidence: 91%
“…The cause of death was mainly related to hemorrhagic shock. Gad et al [9] analyzed TAI in 248 Egyptian cases (69% blunt and 31% penetrating) and reported 26% overall mortality rate in terms of 58% in penetrating and 12% in blunt trauma . The higher mortality rate was due to delay in treatment, a factor that was not measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most abdominal traumas result from motor vehicle accident, fall, interpersonal violence and only rarely from suicidal attempt [1, 2]. The radiological assessment includes a focused assessment with sonography in trauma (FAST), and, in stable patients, an abdominal computer tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…It implied multidisciplinary management, especially related to the presence of a complete disruption of the pancreatic duct. Only few cases of crossbow suicidal attempts were reported throughout the world, most of which are from forensic studies, as such injuries are most often fatal [1]. Beyond the description of the case, we discuss the management of complex pancreatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Abdominal penetrating trauma includes sharp objects damage (stab wound) and gunshot damage (gunshot wound). 4 It is more common in men than women. The most common cause is the knife; the average age of patients is in the third decade of life.…”
Section: Introductionmentioning
confidence: 99%